2019
DOI: 10.1111/faf.12431
|View full text |Cite
|
Sign up to set email alerts
|

Choosing best practices for managing impacts of trawl fishing on seabed habitats and biota

Abstract: Bottom trawling accounts for almost one quarter of global fish landings but may also have significant and unwanted impacts on seabed habitats and biota. Management measures and voluntary industry actions can reduce these impacts, helping to meet sustainability objectives for fisheries, conservation and environmental management. These include changes in gear design and operation of trawls, spatial controls, impact quotas and effort controls. We review nine different measures and actions and use published studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 87 publications
(148 reference statements)
3
50
0
Order By: Relevance
“…As estuarine benthic species, A. hexanema and C. abbreviatus showed a wide niche breadth and high competitiveness in the Min River Estuary [20]. However, in recent years, the extensive use of bottom trawls seriously damaged the population, as well as the seabed environment [56]. Responsive management strategies should be implemented immediately before the population collapse of these species.…”
Section: Discussionmentioning
confidence: 99%
“…As estuarine benthic species, A. hexanema and C. abbreviatus showed a wide niche breadth and high competitiveness in the Min River Estuary [20]. However, in recent years, the extensive use of bottom trawls seriously damaged the population, as well as the seabed environment [56]. Responsive management strategies should be implemented immediately before the population collapse of these species.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, largest impacts occurred when increasing the trawling frequency from 0 to 1 trawling event per year, and the response of mineralization processes to increased trawling frequency was often non-linear, making them more difficult to predict. This would imply that management strategies aimed at maintaining the ecosystem functions provided by shelf sediments should be focused on spatial controls, bottom impact quotas, and effort control, rather than on technical improvements to the trawling gear that per definition require contact with the bottom to catch commercially viable target species (McConnaughey et al, 2020). An effective strategy limits the impacted surface area, and allows carbon stocks and faunal communities in the sediment to recover from a disturbance, resulting in the recovery of vital biogeochemical functions such as denitrification and carbon burial.…”
Section: Reducing Gear Penetration Depthmentioning
confidence: 99%
“…To reduce fishing impacts, alternative bottom trawl gears such as pulse fishing gears are being investigated (Van Marlen et al, 2014;McConnaughey et al, 2020). With pulse gears, the heavy tickler chains are replaced by electrodes, which emit electrical pulses that induce a cramping response in flatfish (Soetaert et al, 2015).…”
mentioning
confidence: 99%
“…Gorgonian coral species in canyon systems of the western Ligurian Sea (northwestern Mediterranean Sea) were found to be negatively impacted by one or more types of derelict fishing gear, with fishing nets causing the greatest impact at most study sites (Giusti et al, 2019). McConnaughey et al (2019) reviewed nine different management measures and voluntary industry actions to reduce adverse impacts from bottom trawl fishing and found that risks and benefits of such efforts depend on the specific fishery and the characteristics of the ecosystem; no universal best practice was apparent due to the diversity of policy drivers that influence the management of fisheries and their environmental impact. In the Northwestern Hawaiian Ridge and Emperor Seamounts, despite significant evidence of adverse impacts from decades (1960s-1980s) of bottom trawling and coral tangle net fishing including scarred hard bottom habitat, coral rubble, and lost fishing gear, Baco, Roark, and Morgan (2019) reported multiple signs of recovery in benthic seamount communities that have been protected for more than 30 years.…”
Section: Effects Of Fishing and Aquaculturementioning
confidence: 99%